please answer this question
Attachments:
![](https://hi-static.z-dn.net/files/d38/7743c08818e548772275be4f40a43319.jpg)
Answers
Answered by
0
Answer: HOPE IT'S USEFUL DEAR
PLEASE MARK ME AS A BRAINLIEST PLS
Step-by-step explanation:
(5x+2)(2-3x) - (x-3)(x+2)
= [5x(2-3x) +2(2-3x) ] - [ x(x+2) -3(x+2)]
= 10x-15x²+4-6x - (x²+2x-3x-6)
= 4x-15x²+4 -x²-2x+3x+6
= -16x² +5x+10
Similar questions
Accountancy,
1 month ago
Science,
1 month ago
Math,
3 months ago
Chemistry,
3 months ago
Physics,
11 months ago